Value of maximum alactic performance in the formation of a sports result of elite cross-country female skiers in competitions at various distances - Golovachev, A. I.; Kolykhmatov, V. I.; Shirokova, S. V. (Sovremennye voprosy biomediciny, 2020)
The article presents the results of a study of the correlation relationship of indicators of maximum alactate power productivity with the sports result of elite cross-country female skiers in the main competitions at various distances of the sports season 2017-2018. The study involved 18 elite female skiers, specializing in various types of competitive activities, aged from 20 to 27 years. Functional surveys were conducted in the laboratory of cyclic Olympic sports of the Federal scientific center of physical education and sport (Moscow). The test program included an assessment of the speed and maximum alactic power of the female skiers by performing a series of accelerations on a cycle ergometer. The obtained indicators of maximum alactic performance were subjected to a correlation analysis with the results at the goal-setting starts of the sports season 2017-2018. The results of the study made it possible to establish the most informative indicators of maximum alactate productivity, which determine the effectiveness of performance at different distances of the cross-country skiing races, and allowed us to determine the existing patterns of manifestation of the speed ability and maximum alactic power depending on the specifics of the competitive activity of female skiers.